A regional, S-dipping late Early to Middle Ordovician palaeoslope in the Brabant Massif, as indicated by slump folds (Anglo-Brabant Deformation Belt, Belgium) - Debacker, Timothy; De Meester, Els (2009)
Within the upper Lower to Middle Ordovician directly north of the Quenast plug (Senne valley, Brabant Massif) numerous pre-cleavage folds and associated detachments occur. These folds and the associated detachments are attributed to slumping. On the basis of a combination of a) the mean axis method, b) the separation arc method, c) the axial-planar intersection method and d) the fold hinge azimuth and interlimb angle method a SSE-dipping palaeoslope is inferred from these Slump features. This is fully compatible with the palaeoslopes inferred by two previous studies on slump folds in other upper Lower to Middle Ordovician outcrop areas of the Brabant Massif. Combined, the results indicate that during the late Early to Middle Ordovician a regionally persistent S-dipping palaeoslope existed within the southern part of the Brabant Massif, with an along-strike length of at least 30 kill. Slumping is attributed to slope failure due to seismic loading by normal faulting related to the separation of Avalonia from Gondwana. In this respect, the regional S-dipping palaeoslope may correspond to bedding tilted by antithetic (N-dipping) lystric faults, or to synthetic (S-dipping) normal fault scarps.